Efficiency Analysis of Incinerator Combustion Chamber Using Variations in the Number of Burners with the Computational Fluid Dynamics Method - Siana, Nezar Azali; Mujiarto, Sigit; Purnomo, Sigit Joko; Saleh, Arif Rahman (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2025)
Waste is a global environmental problem that is increasing with population growth and consumption. Based on SIPSN 2023 data, waste generation in Indonesia reached 69.9 million tons, dominated by food waste (41.60%) and plastic (18.71%), with households as the main source (44.37%). Incinerators are an effective solution to reduce waste volume by 50–90% and have the potential to generate energy through heat conversion. This study designed an incinerator with a capacity of 45 kg with a double burner system fueled by Compressed Natural Gas (CNG) to optimize the combustion process and reduce emissions. The design was carried out using SolidWorks 2022, while flow and emission simulations were carried out using ANSYS 2023 R1. This study compares the combustion performance of single-burner and double-burner systems based on CO and CO2 exhaust emissions. Simulation results show that the single-burner system produces a CO mass fraction of 0.6144 and CO₂ of 0.1452, while the double-burner system produces a CO fraction of 0.6845 and CO₂ of 0.0910. The combustion efficiency of the single-burner system was recorded at 19.1%, while the double-burner system only achieved 11.7%. These values indicate that the single-burner system has more complete and efficient combustion than the double-burner system, in terms of exhaust.